Dominant immune response to HLA‐B57/B58 molecules after platelet transfusion. Issue 12 (10th October 2020) - Coombs, Justine; Ben Hassen, Latifa; Leclerc, Mathieu; Tamagne, Marie; Pannetier, Louise; Khelfa, Mehdi; Delorme, Adèle; Bocquet, Thibaut; Maury, Sébastien; Pirenne, France; Ansart‐Pirenne, Hélène; Vingert, Benoît
Abstract: Background: Patients with hematologic malignancies require prophylactic or curative platelet transfusions to prevent or treat bleeding. Treatments such as chemotherapy, radiotherapy, and hematopoietic stem cell transplantation cause persistent thrombocytopenia, necessitating platelet transfusions. However, class I HLA antibodies can cause a serious complication: immune‐mediated platelet refractoriness. The mechanisms of alloimmunization are incompletely understood. We explored the immunogenicity of HLA molecules and the phenotype of the HLA‐specific CD4 + T cells involved in alloimmunization. Study Design and Methods: We investigated the role of HLA molecules in platelet transfusion immunogenicity in a retrospective cohort study on men with specific anti‐HLA who had undergone transfusion. We investigated the presence and phenotypic profile of HLA‐specific CD4 + T cells in alloimmunized patients included in long‐term platelet transfusion programs for hematologic malignancies. Results: More than 50% of the transfused subjects displayed an antibody response against HLA‐B57 or ‐B58. HLA‐B57–specific CD4 + T‐cell responses were observed in patients alloimmunized against HLA‐B57. Following specific stimulation, the patients presented HLA‐specific CD4 + T cells producing tumor necrosis factor‐α, interleukin (IL)‐13, IL‐17A, IL‐2, IL‐10, and IL‐21. Conclusion: These results shed light on posttransfusion class I anti‐HLA alloimmunization mechanisms and constitute a first step toward developing new strategies for reducing refractoriness.